Assessment of Nurses' Knowledge toward Children with GuillainBarre Syndrome at Pediatric Hospitals in Baghdad City - Kudhaer, Weaam; Mua’ala, Eqbal (Iraqi National Journal of Nursing Specialties, 2010)
Objectives: The study aimed to assess the level of pediatric nurses' knowledge toward children with Guillain-Barresyndrome (GBS) and to find out the relationships between nurses' knowledge and their demographic data.Methodology: A purposive “non probability” sample of (30) nurses was selected from medical neurological wards andRespiratory Care Units of Children Welfare Pediatric Teaching Hospital, Child’s Center Pediatric Teaching Hospital,AL-Kadhemia Teaching Hospital, Baghdad Teaching Hospital, and Neurological Science Hospital which has startedfrom March 5th 2009 to April 30th 2009. The study instrument consists of two parts. The first part is concerned withnurses' demographical characteristic and the second one is concerned with nurses’ knowledge which is divided into twosections. Section one consists of (20) items which are related to nurses’ knowledge about general information ofGuillain-Barre Syndrome, and section two (12) items concerning nurses’ knowledge in relation to nursing care of GBS.Data were collected through a special constructed questionnaire format which includes multiple choice questions. A selfadministrationmethod was used. Data were analyzed by using SPSS packed version (10.0), a descriptive statisticalanalysis (frequencies, percentage, quartile, and mean of scores), and inferential statistical analysis (chi-square) wereused.